Revisiting the improvement of the criminal legislation of the republic of Kazakhstan on liability for the murder for hire - Biyebayeva, A.A.; Kalguzhinova, А.М.; Zhumasheva, А.T. (Bulletin of the Karaganda University “Law Series”, 2020)
The article is concerned with consideration of the signs of murder for hire, the identification of types of accomplices in the commission of murders for hire, the concept of hiring in the commission of a killing, the social grounds for increasing responsibility for these circumstances qualifying the killing. The authors carried out a historical and legal analysis of the customary law of Kazakhs, Soviet and modern domestic criminal legislation regulating responsibility for murders. The bases of differentiation of criminal responsibility for aggravated killing have been determined. The concept and signs of the composition of murder for hire are analyzed, the reasons for the imperfection of the legislative formulation of this aggravating sign are revealed. The empirical basis of the study is composed of the statistical data of the Committee on Legal Statistics and Special Records of the General Prosecutor's Office of the Republic of Kazakhstan, analytical reviews, generalizations of judicial practice, published judicial practice of consideration of criminal cases on murders, as well as materials of criminal cases, acts of the «Taldau» forum, intended to ensure monitoring the quality of judicial acts, analysis of the results of the current activities of the courts, information support for litigants, practicing lawyers, use in scientific and research activities. The reliability of the obtained results is determined by the research methodology, analysis of theoretical and practical data. Studying the issues of correct legal assessment and effective prevention of the murder for hire, analysis of the ways of legal expression of this feature in the norm of criminal law constitute an important direction in the development of criminal law theory, designed to ensure the transition from the empirical basis of legal education to scientific one.